The Sociology of Shari'a: Case Studies from around the World - Possamai, Adam; Richardson, James T.; Turner, Bryan S. (Boundaries of Religious Freedom: Regulating Religion in Diverse Societies, 2015)
This edited volume offers a collection of papers that presents a comparative analysis of the development of Shari'a in countries with Muslim minorities, such as America, Australia, China, Germany,  Italy, Singapore, South Africa and the Philippines, as well as countries with Muslim majorities, such as Malaysia, Bangladesh, Turkey, and Tunisia. The Sociology of Shari'a provides a global analysis of these important legal transformations and  examines the topic from a sociological perspective. In addition, the third part of the book includes case studies that explore some ground-breaking applications of theoretical perspectives such as those from Chambliss and Eisenstadt.